(untitled) (Italian Journal of Public Health, 2005)
Background. Evidences indicate an involvement of apoptosis related genes in gastric carcinogenesis. We studied the gene and protein expression patterns of bcl-2, bax and bcl-X in samples of gastric adenocarcinoma. The apoptotic index values, histological type, differentiation grade, cancer stage and lymph node status were statistically analysed for possible correlations with expressional data. Methods. Thirty specimens of gastric cancer and respective normal control gastric mucosa were collected from patients with the diagnosis of gastric adenocarcinoma who underwent a curative gastrectomy. bcl-2, bax and bcl-XL mRNA and protein levels were respectively determined by reverse transcription PCR (RT-PCR) and western blot using monoclonal antibodies for immunodetection. Results and conclusions. We observed a significant suppression of bax with an increase of bcl-XL at protein and mRNA levels. The presence of lymph node metastases was statistically related to the loss of bax overexpression. Bcl-XL was mostly up-regulated in intestinal/mixed types of gastric carcinoma. The expression patterns described confirm the role for these apoptosis genes in gastric adenocarcinoma.